The Influance Of Digital Marketing, Product Innovation, And Brand Equity On Competitive Advantage Of UMKM Sambal Dede Satoe - Aisyah Putri Andini; Hamidah Hendrarini; Nuriah Yuliati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study was conducted at UMKM Sambal Dede Satoe in Surabaya. The high level of competition among chili sauce micro-enterprises and packaged chili products serves as the background of this research, focusing on the aspects of digital marketing, product innovation, and brand equity. The purpose of this study is to analyze the influence of digital marketing, product innovation, and brand equity on competitive advantage at UMKM Sambal Dede Satoe. This research employs a quantitative approach by distributing questionnaires to 65 consumers of Sambal Dede Satoe. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results indicate that digital marketing and brand equity have a positive and significant effect on competitive advantage, while product innovation shows a positive but not significant effect. These findings suggest that digital marketing and brand equity are the strongest factors in enhancing competitive advantage at UMKM Sambal Dede Satoe, whereas product innovation remains incremental and has yet to produce a significant impact. This study is expected to provide practical insights for UMKM Sambal Dede Satoe in strengthening their competitive advantage, particularly through improvements in digital marketing, product innovation, and brand equity.